PENERAPAN KURIKULUM 2013 DALAM PEMILIHAN KARIR SISWA - Artika Setiawati; Lisnawati Dewi (IKIP Siliwangi, 2019)
The 2013 curriculum was prepared with the hope of producing a generation that could face the future. BK teachers have an important role in the implementation of the 2013 curriculum. With the 2013 curriculum, students are expected to have active, creative, and innovative characters in learning activities and have a mandatory character in decision making. The role of BK teachers is to help or facilitate students to grow and develop their potential and help plan and decide on a career for the future. Specialization of students, facilitated by guidance and counseling, does not end in determining choices and decisions in the chosen field of expertise, but must be followed by educational services that educate, broad developmental accessibility, and preparation of a supportive learning development environment.Keywords: 2013 Curriculum, Role of BK Teachers, Career Specialization.